MARKETING EFFICIENCY OF MILK COWS LOCALLY PRODUCED IN BAGHDAD FOR SEASON 2014 - & HASSAN, AHMAD (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The study focused on the reality of the production and marketing of milk cows in the Abu Ghraib area, located in the western part of Baghdad, as it collected a sample of (127) product milk cows, and the sample was selected at random. Find targets of production and marketing costs and estimate the index marketing efficiency, while the total costs for the production of one kg of the study in small, medium and large fields amounted to about (272.62, 235.48, 209.70) dinars respectively. With regard to total marketing costs by producers in the three fields on the market about (15.17, 6.39, 4.74) dinars kg respectively, finally came the marketing efficiency index of one kg in the three fields towards (69.68, 68.19, 65.96%) respectively. Conclusions of the study it has been shown that the high prices of raw materials, which is the price of the herd and feed led to the weakening profitability of milk from the herd, thereby hindering the entry of new investors. The recommendations that came in the study it has been shown that the state should concern producers and provide the necessary support in the provision of raw materials at a reasonable price and that contribute to the establishment of such projects.